Awareness and implementation of food quality standards under MARDI’s entrepreneurship programmes - Rozhan Abu Dardak (2023)
Consumers are increasingly concerned about food quality and safety. This is evidenced by consumer preference towards products bearing standard logos related to food safety and quality, such as Halal, Good Manufacturing Practice (GMP), ISO 9001:2000 and Hazard Analysis Critical Control Point (HACCP). This study examined the awareness of the food-processing entrepreneurs towards food quality standards and its effects on business performance. This study involved 100 entrepreneurs who received consultative guidance from MARDI. The study revealed that more than 90% of respondents recognized the importance of food quality standards and its impact towards company’s performance. However, only 70% of the respondent used this quality standard. The quality standards mostly used by the entrepreneurs were GMP (60%), followed by Halal (43%) and HACCP (14%). Consultative services and training on the implementation of quality standards such as GMP, Halal and HACCP were the main programmes provided by government agencies, including MARDI. The main factor that influenced entrepreneurs to implement the quality system was their self-motivation to ensure that their products would be accepted by consumers, followed by the advisory of the extension workers. This study also revealed that the main factor that prevented the entrepreneurs from implementing the quality system was the higher cost of getting the certificate and the development cost of the factory to meet the standards.